Analysis of Financial Distress with Springate and Method of Grover in Coal In BEI 2012 - 2016 - Hungan, Agnes Gracia Devina; Sawitri, Ni Nyoman (International Business and Accounting Research Journal, 2018)
The coal industry is one of the largest contributors to the state budget of more than 40 billion annually, so the declining coal industry and the condition of every coal company in Indonesia are of particular concern to the government. This study examines how the level of financial distress of coal mining companies IDX 2012 - 2016 when analyst with Springate method and Grover method, and which method is most appropriate in predicting financial distress in coal companies. From the results of the calculation with the both methods are Obtained results there are some coal companies are declared to have financial distress with both methods and obtained the result that the Grover method is the most appropriate methods in predicting financial distress.